2003
DOI: 10.1016/j.mrfmmm.2003.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and human DNA metabolism: the magic and the mystery

Abstract: The ability of caffeine to reverse cell cycle checkpoint function and enhance genotoxicity after DNA damage was examined in telomerase-expressing human fibroblasts. Caffeine reversed the ATM-dependent S and G2 checkpoint responses to DNA damage induced by ionizing radiation (IR), as well as the ATR-and Chk1-dependent S checkpoint response to ultraviolet radiation (UVC). Remarkably, under conditions in which IR-induced G2 delay was reversed by caffeine, IR-induced G1 arrest was not. Incubation in caffeine did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 57 publications
7
58
1
Order By: Relevance
“…We therefore examined the ability of T cells from C57BL/6 mice to proliferate in response to anti-CD3 and anti-CD28 Abs in the presence of caffeine, which is known to inhibit Atm. Caffeine concentrations of 1 mM inhibit Atm, but not ATR function in vitro and caffeine concentrations of 3 mM inhibit both Atm and ATR function by 50% (22,23). Stimulation of C57BL/6 T cells with anti-CD3 and anti-CD28 in the presence of caffeine induced T cell apoptosis (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…We therefore examined the ability of T cells from C57BL/6 mice to proliferate in response to anti-CD3 and anti-CD28 Abs in the presence of caffeine, which is known to inhibit Atm. Caffeine concentrations of 1 mM inhibit Atm, but not ATR function in vitro and caffeine concentrations of 3 mM inhibit both Atm and ATR function by 50% (22,23). Stimulation of C57BL/6 T cells with anti-CD3 and anti-CD28 in the presence of caffeine induced T cell apoptosis (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…To explore this possibility, we tested whether cell cycle arrest could be prevented by the addition of caffeine. Although caffeine has pleiotropic effects on cells, it is an effective inhibitor of ATM and ATR and has been used to abrogate DNA damage checkpoints in a variety of organisms, including Tetrahymena (24,26,48). For example, the addition of caffeine to Tetrahymena cells that have suffered DNA damage during S phase abrogates the intra-S-phase checkpoint and allows the cells to resume proliferation (48).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 illustrates the well-known effect of 1 J/m 2 UVC on this distribution and the abrogation of the response by caffeine. 15,42 As mentioned in the Introduction, the selective inhibition of incorporation of radiolabeled DNA precursors into low molecular weight nascent DNA has been used as a reliable and reproducible indicator of the activation of the S checkpoint, which results in the inhibition of initiation of new replicons. In the present study, the abrogation of this S-checkpoint response was demonstrated by transfecting HeLa cells with RNAi to knock down specifically the expression of the checkpoint kinase Chk1.…”
Section: Resultsmentioning
confidence: 99%